Aldehyde dehydrogenase 1 (ALDH1) immunostaining in axillary lymph node metastases is an independent prognostic factor in ALDH1-positive breast cancer - Xin Guan; Yi Dong; Zhimin Fan; Yue Zhan; Xinpeng Xie; Gege Xu; Yu Zhang; Guoqiang Guo; Aiping Shi (Journal of International Medical Research, 2021)
Objective To determine whether aldehyde dehydrogenase 1 (ALDH1) immunostaining in axillary lymph node metastases in patients with breast cancer is associated with poor clinical prognosis. Methods This retrospective study reviewed data from the medical records of patients with immunohistochemistry-confirmed invasive ductal carcinoma (IDC) and 1–3 metastatic lymph nodes in the ipsilateral axilla between December 2012 and July 2015. The association between ALDH1 immunostaining in axillary lymph node metastases and clinical parameters and prognosis was analysed using χ 2 -test, Kaplan–Meier survival analysis, univariate and multivariate Cox regression analyses. Results A total of 229 patients with IDC were enrolled in the study. The median follow-up was 61 months (range, 20–89 months). Patients with ALDH1-positive axillary lymph node metastases had significantly shorter relapse-free survival and overall survival compared with those with ALDH1-negative axillary lymph node metastases. ALDH1 immunostaining in axillary lymph node metastases was a significant predictor of poor prognosis in univariate and multivariate analyses. Conclusion This large study with long-term follow-up suggests that ALDH1 immunostaining in axillary lymph node metastases is an independent predictor of poor prognosis in patients with breast cancer. The clinical relevance of this finding should be confirmed in further well-designed prospective studies.